DIAGNOSING STUDENTS' READYNESS TO EDUCATIONAL PRACTICE (Pedagogy of Higher and Secondary Education, 2008)
In the article the problem of readiness of students o f peduniversits is examined to implementation of professional activity in the conditions of modern school.